Clostridium butyricum alleviates LPS-induced acute immune stress in goats by regulating bacterial communities and blood metabolites - Zhang, Chengrui; Hou, Tingyi; Wang, Jihong; Yu, Qingyuan; Zhang, Yonggen; Sun, Yukun (Frontiers in Immunology, 2023)
The mitigation and prevention of acute immune stress are essential for livestock production. Clostridium butyricum (C. butyricum) has shown positive effects in stabilizing intestinal flora disorders, improving immune function and inhibiting disease development, but its effects on ruminants are unclear. Therefore, the current trial was hypothesized that C. butyricum could improve goats' immune function and antioxidant capacity by regulating bacterial communities and blood metabolism and effectively alleviating the acute immune stress induced by LPS. Sixteen healthy goats were fed C. butyricum for 70 days, and the goats were challenged with LPS on day 71. Blood and feces were collected at 0 h and 6 h after the challenge to evaluate the effects of C. butyricum on their intestinal microbiota, immune function, antioxidant function, and plasma metabolites. The results showed that C. butyricum had no significant effect on plasma biochemical parameters at the beginning of the LPS challenge. Still, supplementation with C. butyricum significantly increased plasma levels of IgA, IgG, T-SOD, and T-AOC (P < 0.05), but TNF-α, IL-6, and MDA were strongly decreased (P < 0.05). In contrast, IL-10 showed an increasing trend (P < 0.10). Rectal flora analysis showed that C. butyricum significantly increased the relative abundance of Epsilonbacteraeota at the phylum level of goats; at the genus level, the relative abundance of Campylobacter and Anaerorhabdus]_furcosa_group was also significantly increased (P < 0.05). Christensenellaceae_R-7_group as the dominant flora also showed a significant increase in their abundance values, while Clostridium and Lachnospiraceae_UCG-001 were significantly lower (P < 0.05). When the LPS challenge continued up to 6 h, C. butyricum still resulted in significantly higher plasma concentrations of IgA, IL-10, and T-SOD in goats than in control, effectively reducing TNF-α levels (P < 0.05). In addition, plasma levels of T-CHOL and LDL were significantly reduced, and the expression of d-proline was significantly upregulated according to metabolomic analysis (P < 0.05). In conclusion, dietary supplementation with C. butyricum helped optimize the expression of bacterial communities and blood metabolites to enhance the ability of goats to alleviate acute immune stress.